(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The importance of this research is that it sheds light on an important and vital aspect of the aesthetic artistic production of the civilization of Mesopotamia, especially the Assyrian civilization in particular, which is ornaments and decorations in the New Assyrian period (911-612 BC). It abounds in all aspects of artistic and aesthetic creativity, and it is associated with the customs and traditions of the Assyrian society, which is characterized by originality and wide cultural heritage as well as identifying the craftsmanship of the ancient Assyrian artist and jeweler and also showing the aesthetic features of the artistic production of the ancient Assyrian civilization. Ornaments and decorations are considered as a mirror which reflects the aesthetic concept and a manifestation of artistic taste and one of the phenomena of its development. Itt is a study of the customs and traditions of society, as it is the study of the human connections between its members as well as showing the jewelry tastes and aesthetic concept and spiritual tendencies and material possibilities. There is no doubt that the flourishing of jewelry in a society is greatly influenced by the level of economic life of that society, its industrial sophistication, business activity and social history. In addition, the jewelry industry is a form of our fine arts that should be studied.